Utilizing Paper-mode Quizizz for formative assessment in English teaching and learning - Rizal Wahid Permana Putra (Journal of Research on English and Language Learning (J-REaLL), 2023)
As information and communication (ICT) has grown rapidly, there are many forms of technology provided to support and facilitate the teaching and learning process. Game-based learning these days has been growing interest. It is not only purposed for the teaching-learning media but also for the assessing phase. Quizizz is one of game-based learning platforms offering multiple tools to assess the students’ learning progress. It provides Paper-mode quizzes using printable or a quick-response code. In this research, the researcher deals with utilizing Paper-mode Quizizz for formative assessment in English teaching and learning. This research is a case study with qualitative data conducted at SMP SSA Negeri Kloposawit 1 Candipuro involving 41 students from 8A and 8C as the research participants. Further, to obtain the students’ perceptions, the researcher collects the data through interviews. The result indicates that most students show positive perceptiveness in utilizing Paper-mode Quizizz for formative assessment in teaching and learning English. It is stated that Paper-mode Quizizz is easy to use, enjoyable, fun, challenging, and very interesting. The students only show and rotate the answer, and the teacher will scan the code cards to display the real-time results. In addition, this makes students more motivated to have a test using Paper-mode Quizizz. To sum up, Paper-mode Quizizz is an effective-alternative platform to use for formative assessment in English teaching and learning.